The structural and semantic characteristics of the phraseological terminological syntagm in scientific language of modern economics - Pyatetska, Olga (Current issues of Ukrainian linguistics: theory and practice, 2017)
The article analyzes the structural features of economic terminological syntagm of idiomatic type. The author defined semantic and grammatical modifications in economic terminological syntagm that underlie in their creation. The research shows that terminological word-combinations that appeared as a result of translation from English with the conservation of secondary nomination are selected and analyzed.